IMPLEMENTASI PENDEKATAN SAINTIFIK BERBANTUAN MEDIA GAMBAR PADA PEMBELAJARAN TEKS FABEL DI KELAS VII MTs AL-IHSAN BATUJAJAR - Siti Jubaedah (IKIP Siliwangi, 2020)
The 2013 curriculum is a curriculum that has been established by the government in the world of education in Indonesia. Fable literature is one of the teaching material that is learned in class VII even semester. This research is based on the researchers' curiosity on the implementation of scientific approaches and media images in learning fable text in class. The thing measured in this study is student learning outcomes after the application of learning with the methods and media that have been used. The reason for this research is to find out the implementation of scientific approaches and media images on learning fable texts. Subject analyzed was 33 people in VII B class. From data collection resulted by multiple choice based test as much as 10 questions, the data was generated about 20 people fulfilling the threshold criteria with percentage of 60,6% while the other 13 people did not fulfill the threshold criteria with percentage of 39,4%. Most of the students made mistakes in answering question 3 and question 5. From all 33 students, there are 14 students that answered question 3 correctly and 11 students that answered question 5 correctly. The implementation of scientific approach with flashcard/picture to students lerning outcomes has been successfully applied in the field. It was could be seen through measuring result that has been done at the end of learning fable texts.